Nilai Pendidikan Karakter dalam Tradisi Lokal - Bani Sudardi (Madaniyah, 2014)
Local traditions contain character educations for their owner. Every people has specific in character education. Cheater education has to uncover from culture elements; language, literature works, customs, and so on. In this era we see our nation take away their character educations that they have get them for centuries to take care of their identities. The put foreign culture (pop, trend), but in the next time it show us many problems have to be solved.